Uncovering pre-cytokinetic block in cancer cells under shear stress using a disturbed flow-generating device - Beresova, Lucie; Vitecek, Jan; Protivánková, Iva; Dudka, Michal; Chroma, Katarina; Skrott, Zdenek; Buchtova, Tereza; Poláková, Kamila; Novotny, Jan; Novakova, Ludmila; Bártek, Jiří; Mistrik, Martin (Scientific reports, 2025)
During metastasis, cancer cells navigate through harsh conditions, including various mechanical forces in the bloodstream, highlighting the need to understand the impact of mechanical and shear stresses on cancer cells. To overcome the current methodological limitations of such research, here we present a new device that replicates similar conditions by applying shear stress on cultured cells. The device provides a less complex, easily accessible alternative to traditional fluidics while generating fluid shear stress values comparable to those in human veins and capillaries. The device allows analyses of large cell numbers in standard cell culture flasks and incubators. Using this device to explore the shear stress-induced responses of various human cell lines, we discovered a previously unknown, reversible pre-cytokinetic block occurring in cells that lose anchorage during mitosis and are kept under constant shear stress. Notably, some cancer cell lines appear to bypass this unorthodox cell-cycle block, suggesting its role as a safety checkpoint to restrict the proliferation of cancer cells in the bloodstream and their overall spreading potential. These findings provide new insights into the diverse responses of normal and cancer cells to shear stress and highlight the potential of our technology for research on circulating tumor cells and metastatic spread.
Keywords: Mitosis; nádorové buněčné linie; nádory; Shear Strength; Stress, Mechanical; pevnost ve smyku; Neoplastic Cells, Circulating; Cell Line, Tumor; Humans; mitóza; lidé; proliferace buněk; Cell Proliferation; Neoplasms; nádorové cirkulující buňky; mechanický stres